The teaching rose in distance education: new perspectives for pedagogical work (Research, Society and Development, 2020)
In recent years, there has been a significant growth in the offer of distance learning courses and the need for training teachers who can act and meet this logic and the context mediated by Information and Communication Technologies (TICs). This text intends to discuss the role of teachers and their performance in the Higher Workplace Safety Course in distance learning. It is intended, therefore, to present the theoretical foundation that substantiates the pedagogical action of the teacher in the face of the work carried out in higher education courses, as well as the role performed in relation to the work developed in Higher Education in Distance Education. This qualitative research is characterized as exploratory and descriptive, with approaches to the case study and bibliographic and documentary research. Observations were made during pedagogical workshops with 11 teachers who work in distance education at the State University of Maranhão. The data obtained were analyzed using an approximation with the Bardin Content Analysis technique. It was observed that the teacher assumes, together with the multidisciplinary team, the challenge of producing materials and technological resources that favor learning, enabling the student to be the active subject. The teacher in this scenario aims to be the mediator, developing important skills as a researcher, encourager and creator of a learning situation that enable teaching in distance learning.